Effects of carbon dioxide on flammability limits of acetylene - Nur Fitriah, Mohd Jaafar (2012)
An experimental study on the effect of carbon dioxide (CO2) dilution on flammability limit of acetylene (C2H2) was performed,for system with various concentration of fuel.The objectives of this experiment were to determine the lower flammability limit(LFL)and upper flammability limit(UFL)of C2H2 and to determine the effect of CO2 on flammability limits of C2H2.The explosion pressure and explosion time were measured using an apparatus called 20 L explosion vessel at operating condition 20 oC and 1 bar.The first part of this experiment was conducted with different percentages of C2H2 without the presence of CO2 to determine the LFL and UFL of pure acetylene at temperature 20 oC and pressure 1 bar.The second part was conducted with different percentage of C2H2 with the presence of 15% of CO2.From the theory, when there is dilution of inert gases in fuel happen, the LFL of the fuel will increase while the UFL of the fuel will decreases,thus the flammability range of those fuel will be smaller.The explosion pressure data was collected to determine the flammability limit of acetylene and also acetylene with the presence of CO2.